PENGEMBANGAN UMKM MELALUI PELATIHAN BRANDING, PEMASARAN DIGITAL DAN PENERAPAN AKUNTANSI BERBASIS APLIKASI DI DESA BINANGA KECAMATAN SENDANA - Hafid, Haeruddin; Novitasari, Eni; Edy, Sri Amalia; Suriadi, A. Nur Farahdiba (Universitas Mataram, 2024)
Binanga Village is one of the villages that has quite a large number of UMKM in Sendana District. Based on observations, UMKM in Binanga Village are still not optimal in running their business. This needs special attention considering that the potential for increasing UMKM is one of the important aspects that can improve the welfare of the community in Binanga Village. Therefore, the service team carries out service activities to help resolve these problems. This service activity is carried out with reference to economic development targets in the form of creating job opportunities and equal distribution of income. The solutions that the service team provides are increasing understanding of UMKM players with product branding training, increasing product marketing with training on the use of digital media in marketing products, and increasing knowledge of application-based accounting in financial recording with training in the application of application-based accounting. As for the results of this service, the partner villages were very satisfied with the training we carried out because it was able to increase the competitiveness of local products in Binanga Village and increase accountability for recording and calculating selling prices and profits.